Evaluation of Antifungal Effectiveness of a Novel Probiotic Toothpaste: An In-vitro Study - Pavita Kataria; Harpreet Singh (Journal of Clinical and Diagnostic Research, 2022)
Introduction: There is increasing public interest in probiotic healthcare products since their discovery by Élie Metchnikoff in the early 20th century. This trend is not only visible in supermarkets and dental practices, but also in the scientific world. An increasing number of clinical trials and laboratory investigations are being conducted to validate the claims made about these products with regards to their antifungal properties. Aim: To evaluate the antifungal properties of commercially available probiotic, anticaries toothpaste, Purexa, against Candida albicans in-vitro. Materials and Methods: An in-vitro study was carried out for a period of three months from December 2021 to February 2022 in the Department of Microbiology, Baba Jaswant Singh Dental College and Research Institute, Patiala, Punjab, India. Two wells were prepared in each blood agar plate containing lawn cultures of Candida albicans. The plates were incubated at 37˚C for 24 hours. Purexa toothpaste was poured into one well as test material. The second well was filled with distilled water to act as control. A total of 10 sample plates were made. Antifungal activity was assessed by measuring the Zone of Inhibition (ZOI) in millimeters (mm) using a digital vernier caliper after 24, 48 and 72 hours, and then after one week. Increasing width of zones of inhibition indicated definite antifungal activity of Purexa toothpaste. A p-value <0.05 was considered to be statistically significant. Results: All the sample plates showed definite zones of inhibition at 24 hours, 48 hours, 72 hours and one week intervals around the wells containing the test material, which indicated antifungal efficacy of Purexa probiotic toothpaste. No inhibition zones were seen around the wells containing distilled water. The mean width, if ZOI was the highest at day 7 (28.71 mm), followed by day 2 (26.66 mm), day 3 (26.36 mm) and least on day 1 (25.25 mm). Conclusion: The preliminary data obtained from the present study indicates the prospective use of Purexa probiotic toothpaste in cases, where antifungal activity of toothpaste is desirable.